Refinements of Inequalities among Difference of Means - Huan-Nan Shi; Da-Mao Li; Jian Zhang (International Journal of Mathematics and Mathematical Sciences)
In this paper, for the difference of famous means discussed by Taneja in 2005, we study the Schur-geometric convexity in (0, ∞) × (0, ∞) of the difference between them. Moreover some inequalities related to the difference of those means are obtained.